Pengelolaan Pembelajaran di Lembaga Bimbingan Belajar Exis Kota Padang - Arif Kushariadi; Solfema Solfema (Jurnal Family Education, 2022)
Tutoring institutions are part of the educational path outside the school which aims to serve the community. The role of tutoring institutions is very important, especially among school students, ranging from elementary school, junior high school, final high school. As well as any factors that affect the management of learning at the Exis Kota Padang Tutoring Institute. The sub-variables are focusing on learning planning, learning organizing, learning implementation, and learning evaluation. This research uses a quantitative descriptive type approach. The population taken in this study is students who follow tutoring at the Exis Kota Padang tutoring institution. Sampling technique is random sampling, the sample taken is 20% of each level of education in the study institution Exis Kota Padang which amounted to 42 people. Data collection techniques use questionnaires. Then the data collection tool used is through questionnaires and google form. In data analysis techniques use percentage formulas. The results of the research obtained, namely first, in the learning planning made by the institution proved to run well and correctly it can be seen from the alternative answers given and most respondents answered very satisfactorily. Second, in organizing the learning made by the institution proved to run in accordance with expectations it can be seen from the alternative answers given and most respondents answered very satisfactorily. Third, in the implementation of learning carried out by institutions proved to run well and there are no obstacles that can be seen from the alternative answers given and most respondents answered very satisfactorily. Fourth, in the evaluation of learning conducted by the institution proved to be going well and correctly it can be seen from the alternative answers given and most respondents answered very satisfactorily.